A down‐conversion mixer using 90‐nm CMOS process for 60‐Ghz applications. Issue 10 (October 2014) - Huang, Chia‐Yang; Chang, Yu‐Hsin; Chiang, Yen‐Chung
ABSTRACT This article proposes a double‐balanced 60‐ to 12‐GHz down‐conversion mixer fabricated in the 90‐nm CMOS process. The proposed mixer has a 5.825 dB measured conversion gain and 13–16 dB noise figure. The input P1dB of the mixer is −4.4 dBm and the measured LO‐IF, LO‐RF, and RF‐IF isolations are above 42, 44, and 41.5 dB, respectively. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2456–2458, 2014